Evaluation and efficiency of public spending on R+D+i in science and technological innovation pro-grams administered by Concytec of Peru (LACCEI, 2024)
The research analyzes, based on efficiency, the execution of public spending in the programs of the National Council of Science, Technology and Technological Innovation (Concytec) of Peru contrasting the effect of public investment in R D in relation to GDP and the administration of financial resources allocated in research projects managed by the Fondecyt. Employability employs a cross-sectional mixed approach The main results were determined: lack of efficiency in the allocation of financial resources, the inadequate construction of a transversal policy of the Peruvian State for innovation and scientific development as well as the non-use of information systems for decision-making and management of indicators in innovation programs.